Forecasted Payback Period in the Case of Energy-Efficient Activities - Gorshkov, Alexander; Murgul, Vera; Oliynyk, Olena (MATEC web of conferences, 2016)
There is a very important governmental issue, which is to secure energy efficiency of buildings under design. This issue is stated in the federal law, governmental regulations and orders of the subject Ministries. However, issues related to energy-efficiency are appropriate for both existing buildings and the ones under design. Total volume of buildings constructed according to new heat protection rules and regulations valid since 2000, accounts for 5% of the total volume of all the housing stock in the Russian Federation. Consequently, reduction of heat energy consumption in houses built before 2000 is getting more crucial in the nearest future. Nowadays there is a national programme to execute major repair works in the existing buildings. It is important to have this programme correlated with the energy-saving program. However, the economy of investment projects shouldn’t be disregarded when running this programme. Energy-efficient activities should contribute to a better return on investment, and reduction of the energy consumed.